Dampak Hukum Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja Bagi Pemegang Izin Lingkungan - Bernadette Adinda Galuh Trimillenia Rumadjak; Victor Juzuf Sedubun; Vica Jillyan Edsti Saija (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The presence of changes in licensing in the Job Creation Law has a very big impact on environmental sustainability, this is because there is a missing government authority, changes in the Job Creation Law that change the provisions of the Environmental Protection and Management Act, especially AMDAL and environmental permit.Purposes of the Research: The purpose of this study is to determine and analyze the legal consequences for environmental permit holders after the enactment of the Job Creation Act Number 11 of 2020. Methods of the Research: The method used is a normative legal research method.Results of the Research: The results and discussion have legal consequences for environmental permit holders after the enactment of the Job Creation Act because environmental permits issued after the enactment of the Job Creation Act automatically follow the Act and environmental permits that were in effect before the Job Creation Act remain in force in accordance with Life Protection and Management Law Number 32 of 2009 but if the permit status is to be extended, it must automatically renew the documents because otherwise the permit status is considered to have been completed.